Basic Statistics Relating to the Indian Economy 1950-51 to 1962-63 - Planning Commission (Planning Commission, 1957)
The document provides a comprehensive overview of India's economic growth between 1950-51 and 1962-63, presenting key statistical data from various sectors through notable periods of Five-Year Plans. This document presents a detailed overview of the demographic trends and economic indicators of India, illustrating the complexities of urbanization amid predominantly rural populations and indicating potential areas for economic development. The data emphasizes the pronounced gap between urban and rural demographics and aligns with the nation’s economic growth trajectory over the outlined period.
Statistics and Surveys Division
Statistics and Surveys Division
Keywords: Economic Growth; Agricultural Production; Industrial Production; Foreign Trade; Price Levels; Public Finance; Livestock; Forestry Products; Mining Production; Electricity Generation; Transport and Communications